Diverse Facets of Sphingolipid Involvement in Bacterial Infections - Kunz, Tobias C.; Kozjak-Pavlovic, Vera (Frontiers in Cell and Developmental Biology, 2019)
Sphingolipids are constituents of the cell membrane that perform various tasks as structural elements and signaling molecules, in addition to regulating many important cellular processes, such as apoptosis and autophagy. In recent years, it has become increasingly clear that sphingolipids and sphingolipid signaling play a vital role in infection processes. In many cases the attachment and uptake of pathogenic bacteria, as well as bacterial development and survival within the host cell depend on sphingolipids. In addition, sphingolipids can serve as antimicrobials, inhibiting bacterial growth and formation of biofilms. This review will give an overview of our current information about these various aspects of sphingolipid involvement in bacterial infections.